Pelleting of diet for weaning pigs of different initial weights - Diego Surek (Ciência Rural, 2017)
Physical form effect of the pre-starter diet supplied during the post-weaning period from 21 to 41 days of age on diet digestibility and animal performance in terms of zootechnical performances of light-weight (5.82kg) and heavy-weight weaning piglets (6.32kg) was evaluated, as well as the residual effects of the treatments until slaughter. Forty-eight female pigs at 21 days of age were evaluated. The experimental design was completely randomized in a 2x2 factorial scheme (meal/pelleted diet vs. light-weight/heavy-weight piglets), with six replicates for the nursery phase and 12 replicates for the growing–finishing phases. Animals received the experimental diet from 21 to 41 days of age. Data were analyzed with ANOVA, setting the significance in 5%. Feeding with the pelleted diet resulted in a 39% greater daily weight gain and a 28% greater feed conversion rate for piglets from weaning to 40 days of age. Pelleting also resulted in a decrease in feed wastage during the first week after weaning (9.15% for meal diet vs. 1.68% for pelleted diet) and; consequently, the results showed an increase in feed consumption. Digestible energy of the pelleted diet (3,626kcal kg-1) was greater than that of the meal diet (3,424kcal kg-1). The physical form improved the performance of weaning pigs and the digestibility of the pre-starter diet, but there wasn’t residual effect of the physical form and the weight of a piglet at weaning on live weight at slaughter.